Entry of Human Parechovirus 1 - Joki-Korpela, Päivi (American Society for Microbiology, 2001)
Human parechovirus 1 (HPEV-1) is a prototype member of parechoviruses, a recently established picornavirus genus. Although there is preliminary evidence that HPEV-1 recognizes α(V) integrins as cellular receptors, our understanding of early events during HPEV-1 infection is still very limited. The aim of this study was to clarify the entry mechanisms of HPEV-1, including the attachment of the virus onto the host cell surface and subsequent internalization. In blocking experiments with monoclonal antibodies against different receptor candidates, antibodies against α(V) and β(3) integrin subunits, in particular in combination, appeared to be the most efficient ones in preventing the HPEV-1 infection. To find out whether HPEV-1 uses clathrin-coated vesicles or other routes for the entry into the host cell, we carried out double-labeling experiments of virus-infected cells with anti-HPEV-1 antibodies and antibodies against known markers of the clathrin and the caveolin routes. At the early phase of infection (5 min postinfection [p.i.]) HPEV-1 colocalized with EEA1 (early endosomes), and later, after 30 min p.i., it colocalized with mannose-6-phosphate receptor (late endosomes), whereas no colocalization with caveolin-1 was observed. The data indicate that HPEV-1 utilizes the clathrin-dependent endocytic pathway for entry into the host cells. Interestingly, endocytosed HPEV-1 capsid proteins were observed in the endoplasmic reticulum and cis-Golgi network 30 to 60 min p.i. Depolymerization of microtubules with nocodazole inhibited translocation of the virus to the late endosomes but did not block HPEV-1 replication, suggesting that the RNA genome may be released early during the entry process.